Literature Review: Efektivitas Terapi Musik Klasik Terhadap Gangguan Mental Pada Anak Hingga Lansia - Keissa Nazelina; Ati Kusmawati; Kesya Syafinatunnida; Vinca Anidya (Concept: Journal of Social Humanities and Education, 2024)
The background of this literature review study is the many people still suffer from mental illnesses, and the number of people who suffer from them is growing every year. Types of mental disorders such as depression, anxiety, stress, hallucinations, and others. The purpose of this literature is to see how efficient Classical Music Therapy is at lowering the rate of mental problems in people of all ages, from children to the elderly. The method of literature review review was obtained using the keywords "efficacy of classical music treatment," "impact of classical music therapy," and "mental problems" in the Google Scholar, Garuda, and Mendeley databases. The results of the literature review study based on fifteen journals that have been presented that classical music therapy is effective in reducing the rate of mental disorders in children to the elderly. The journal review found that: 1) Depression is reduced; 2) Anxiety is reduced; 3) Stress is reduced; 4) Hallucinations are reduced; and 5) The psychological improvement. Conclusions from the study of literature, that classical music therapy reduces the risk of mental problems in people of all ages, from children to the elderly This literature review study suggests that classical music therapy can be utilized as a non-pharmacological treatment for those suffering from mental illnesses.